Phylogenetic systematics of the family Sillaginidae (Percomorpha: order Perciformes) - Kaga, Tatsuya (Zootaxa, 2013)
The phylogenetic relationships of the family Sillaginidae are inferred based on morphological characters. The Sillaginidae is revealed as being a monophyletic group supported by 16 synapomorphies such as shortened segments on the first soft ray of pelvic fin and the adductor mandibulae section A2 covering section A1 laterally. The characters recognized in 24 transformation series were used for the phylogenetic analysis to reconstruct the interrelationships of the family. Twelve equally most parsimonious trees were obtained in the analysis. A strict consensus tree from the 12 trees was adopted as representing the phylogenetic relationships of the family Sillaginidae. Although reversals and character changes to other derived conditions are recognized, it is inferred that five characters additionally support the monophyly of the Sillaginidae. The family Sillaginidae is redefined based on the synapomorphies supporting its monophyly for the first time. In the new classification proposed, the Sillaginidae comprises the following five genera: Sillago, Sillaginopsis, Sillaginodes, Sillaginopodys, and Sillaginops gen. nov. A key to identification of the genera of Sillaginidae is provided. The family Sillaginidae contains two groups having different evolutionary trends in the reconstructed phylogeny of the family. The first group, including Sillaginopsis, Sillaginodes, Sillaginopodys, and Sillaginops gen. nov., has a trend towards reducing the swimbladder; and the second group, including only Sillago, has a trend towards further refining the swimbladder.